2016
DOI: 10.1016/j.carbon.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary and curvature enhanced lithium adsorption on carbon

Abstract: a b s t r a c tWhile the speculation that graphene may owe double or even higher capacity of lithium adsorption than graphite does remains speculative, there is growing evidence that defects and edges may promote lithium adsorption on graphene and other nanostructured carbon. Here we report a first-principles study on how grain boundary defects in graphene may influence the adsorption of lithium. The adsorption energy for Li atoms trapping in 5-, 7-, and 8-rings is much lower than the counter-part of Li atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
(33 reference statements)
1
20
0
Order By: Relevance
“…We found that, adsorption kinetic parameters of calcium ion on our oxidized graphene sheets agree with the adsorption nature of the other graphene oxide. Which is produced by another process with increasing adsorption capacity of our graphene oxidized sheets toward calcium ions respecting to other ions in the same rank, so a pseudosecond demand model can be considered (Pang et al 2016, Liu et al 2016aTan et al 2016). The latter is shown that the rate determining step may be chemical adsorption one through the exchange of electrons amidst adsorbent and adsorbate.…”
Section: Effect Of Contact Time and Adsorption Kineticsmentioning
confidence: 99%
“…We found that, adsorption kinetic parameters of calcium ion on our oxidized graphene sheets agree with the adsorption nature of the other graphene oxide. Which is produced by another process with increasing adsorption capacity of our graphene oxidized sheets toward calcium ions respecting to other ions in the same rank, so a pseudosecond demand model can be considered (Pang et al 2016, Liu et al 2016aTan et al 2016). The latter is shown that the rate determining step may be chemical adsorption one through the exchange of electrons amidst adsorbent and adsorbate.…”
Section: Effect Of Contact Time and Adsorption Kineticsmentioning
confidence: 99%
“…As expected, the adsorption energies on different curvature models are gradually reduced as the number of adsorbed Li atoms increases ( Figure 5 d), which mainly originates from the Li–Li Coulombic repulsion. 11 The values of the adsorption energies are still negative, indicating an exothermic and stable reaction. 33 Importantly, even though the Li–Li distance (LiC 2 ) on NEGS is shorter relative to that (LiC 6 ) in the graphene, the adsorption energies of NEGS for LiC 2 remain stronger than that of graphene for LiC 6 with the increase of Li atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, theoretical calculations suggested that the positive and negative curvature structures of the carbon materials not only show a positive effect on Li + adsorption but also lead to three-dimensional Li-ion diffusion paths with relatively low energy barriers. 10 , 11 In fact, the geometric architecture is essentially derived from the transformation of the hybridized orbital types of carbon atoms to generate the response of chemical bonds to bending deformations, 12 thereby resulting in the regulation of the geometric and electronic structures within the atomic-scale scope. 8 , 13 16 However, the underlying reasons for extra capacity have not been uncovered deeply, especially the level of the electronic structure, much less to construct the relationship between non-coplanar sp 2 /sp 3 hybridized orbital and their corresponding Li-ion storage properties.…”
Section: Introductionmentioning
confidence: 99%
“…First-principle calculations [158] based on density functional theory (DFT) revealed that the lithium adsorption on graphene could be enhanced by topological defects including divacancy (5-8-5 rings) and Stone-Wales defect (5-7-5-7 rings) due to the increased charge transfer between the adatom and defected sites in graphene. Later theoretical studies found that not only topological defects like 5-, 7-and 8-rings (Fig 14a-c), but curvatures (Fig 14d) of the graphene sheet could also enhance lithium adsorption resulting in better lithium storage property [159].…”
Section: Topologically Designed Graphene For Novel Energy Related Appmentioning
confidence: 99%